2011
DOI: 10.1111/j.1365-2575.2010.00352.x
|View full text |Cite
|
Sign up to set email alerts
|

Why situational method engineering is useful to information systems development

Abstract: Effective methods and methodologies for building information systems (IS) remain crucial to building successful IS. This paper investigates the use of situational method engineering for IS development (ISD) projects in a professional bureaucracy. This specialist organization methodology (SOM) is built starting with the philosophy of ISD moving through to flexible, amethodical implementation methods, a proposed instance of situational method engineering that is targeted towards professional bureaucracies. An in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 48 publications
(75 reference statements)
1
1
0
Order By: Relevance
“…This research agrees with others who found that in order to increase our understanding of agility beyond the ASD environment, researchers need to consider the ways in which organisations set up their supporting organisational structures and processes (Agerfalk et al, 2009, Lyytinen and Rose, 2006, White Baker, 2011. Our findings suggest that while the Beyond Budgeting model is complementary to an agile systems development (ASD) environment many legacy organisational structures, processes and mechanisms are not suited to an agile way of operating.…”
Section: Implications For Theorysupporting
confidence: 76%
“…This research agrees with others who found that in order to increase our understanding of agility beyond the ASD environment, researchers need to consider the ways in which organisations set up their supporting organisational structures and processes (Agerfalk et al, 2009, Lyytinen and Rose, 2006, White Baker, 2011. Our findings suggest that while the Beyond Budgeting model is complementary to an agile systems development (ASD) environment many legacy organisational structures, processes and mechanisms are not suited to an agile way of operating.…”
Section: Implications For Theorysupporting
confidence: 76%
“…The paper of Elizabeth White Baker (2011) also looks at information systems development but is much more of a philosophical piece. It distinguishes between methods and methodologies and presents a methodology for information systems development as applied to a specific context: a professional bureaucracy.…”
mentioning
confidence: 99%